Implementing and evaluating standardised tuberculosis incident management for nonhousehold contacts in a large clinical network. Issue 3 (6th September 2021) - Patterson, Benjamin; Boparai, Narinder; Dekoningh, Jennifer; Anaraki, Sudy; White, Jacqui; Lipman, Marc
The strategy to eliminate tuberculosis (TB) in low-incidence countries includes the investigation of the contacts of TB cases [1]. This recognises that whilst most TB disease in these settings is due to reactivation [2], local transmission also occurs [3]. In the UK, TB networks (TBN), which support and coordinate local and regional TB services, typically follow the National Institute of Health and Care Excellence guidance which recommends screening close contacts (predominantly household) but not routinely for social or non-household contacts [4]. Many studies from low TB burden countries report contact investigation for specific congregate settings including outbreaks in childcare centres [5], homeless facilities [6] and methadone treatment clinics [7]. However, the comprehensive application of contact investigation across multiple non-household locations is rarely reported. Therefore, we evaluated a systematic approach to managing people potentially exposed to TB in congregate settings. A systematic approach to nonhousehold TB contact identified a similar number of LTBI cases to household screening over the same time period https://bit.ly/2Tq96LN